PROTOTYPE SISTEM NOTIFIKASI MONITORING DAYA LISTRIK DENGAN METODE FUZZY BERBASIS ANDROID - Budianto, Alfa Wahyu; Tri Sulistiyo, Muhammad Priyono; Nugraha, Danang Aditya (Jurnal Fakultas Teknologi Informasi, 2025)
Increasing electrical energy consumption in the household sector is a major concern in effective energy management to prevent waste and reduce costs. Conventional electrical power monitoring systems have weaknesses in terms of time and efficiency because they require manual calculations of the use of each electronic device. The development of mobile technology and the Internet of Things (IoT) offers new opportunities in developing monitoring systems that are more interactive and can be accessed in real-time via Android devices. However, the biggest challenge is presenting power usage information that is easy for users to understand. Fuzzy methods offer a solution by converting numerical data into simpler information such as "high", "medium" or "low" power consumption categories, making it easier for users to understand. In addition, the fuzzy method can also provide warning notifications when power consumption exceeds a certain limit. This research aims to develop an Android-based electrical power monitoring system using the fuzzy method. This system is designed to provide direct and efficient power consumption information, as well as notifications that help users monitor household energy consumption. It is hoped that this system can contribute to better energy management, provide solutions to excessive energy consumption, and become the basis for the development of smart home technology in Indonesia.